2017
DOI: 10.1371/journal.pone.0189437
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring bottlenose dolphin leukocyte cytokine mRNA responsiveness by qPCR

Abstract: Both veterinarians caring for dolphins in managed populations and researchers monitoring wild populations use blood-based diagnostics to monitor bottlenose dolphin (Tursiops truncatus) health. Quantitative PCR (qPCR) can be used to assess cytokine transcription patterns of peripheral blood mononuclear cells (PBMC). This can supplement currently available blood tests with information on immune status. Full realization of this potential requires establishment of normal ranges of cytokine gene transcription level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The broad cross-reactivity suggests that these primer sets are likely to cross react across several other mammalian species. Studies of basal cytokine levels in marine mammals are forthcoming but still limited (Beineke et al, 2007;Beineke et al, 2004;Ferrante, Hunter & Wellehan, 2018;Hofstetter et al, 2017) and, consistent with our study, others have encountered challenges with sensitivity. Sitt et al (2016) determined that IL-4 transcripts were typically absent in killer whales (Orcinus orca) and levels of IL-4 in domestic pig (Sus scrofa) remained low even after lymphocyte stimulation (Murtaugh et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…The broad cross-reactivity suggests that these primer sets are likely to cross react across several other mammalian species. Studies of basal cytokine levels in marine mammals are forthcoming but still limited (Beineke et al, 2007;Beineke et al, 2004;Ferrante, Hunter & Wellehan, 2018;Hofstetter et al, 2017) and, consistent with our study, others have encountered challenges with sensitivity. Sitt et al (2016) determined that IL-4 transcripts were typically absent in killer whales (Orcinus orca) and levels of IL-4 in domestic pig (Sus scrofa) remained low even after lymphocyte stimulation (Murtaugh et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that ConA (a selective T-cell mitogen) induces proliferative activity and gene expression of cytokines in bottlenose dolphins, but no information is available regarding the time course ( Hofstetter et al, 2017 ; Segawa et al, 2013 ; Sitt et al, 2008 ). Previous studies on ConA-induced cytokine mRNA expression levels of cPBMCs only presented one or two time points ( Segawa et al, 2013 ; Sitt et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted on RAW 264.7 cells, which are mouse macrophage cells. Cytokine production tests are considered to be reliable in immunogenicity estimation [ 71 ].…”
Section: Resultsmentioning
confidence: 99%